PERBANDINGAN KUALITAS KARBON AKTIF YANG DIBUAT DARI BATOK KELAPA HIBRIDA DAN BATOK KELAPA DALAM - Tangkuman, Herling (Sam Ratulangi University, 2009)
The objective of this research was to study active carbon quality from hybrid and deep coconut shell. Theparameter to analyze quality of active carbon were water content, ash content, volatile content, bondingcarbon content, Iodine value, and % tetrachloride. The results show that active carbon from deep coconutshell has the best quality in (CTC 54%, Iodine value 904, good granule and low solidity)Â Keywords : Quality, active carbon, hybrid coconut, deep coconut